2020
DOI: 10.3390/nu12092536
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Dietary Patterns and Lifestyles Among Spanish Children in the EsNuPI Study †

Abstract: Dietary patterns (DPs) are known to be tied to lifestyle behaviors. Understanding DPs and their relationships with lifestyle factors can help to prevent children from engaging in unhealthy dietary practices. We aimed to describe DPs in Spanish children aged 1 to <10 years and to examine their associations with sociodemographic and lifestyle variables. The consumption of toddler and young children milk formulas, enriched and fortified milk within the Spanish pediatric population is increasing, and there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…They show that nearly half of children and adolescents whose parents had a university education had high adherence to the Mediterranean diet, whereas the percentage was much lower among children whose parents had a low or medium education level. Outcomes that are consistent with ours in this respect have been observed in studies conducted in various countries [66][67][68][69]. Yañez et al have shown that low family educational level is associated with low adherence to the Mediterranean diet in adolescents [70].…”
Section: Discussionsupporting
confidence: 90%
“…They show that nearly half of children and adolescents whose parents had a university education had high adherence to the Mediterranean diet, whereas the percentage was much lower among children whose parents had a low or medium education level. Outcomes that are consistent with ours in this respect have been observed in studies conducted in various countries [66][67][68][69]. Yañez et al have shown that low family educational level is associated with low adherence to the Mediterranean diet in adolescents [70].…”
Section: Discussionsupporting
confidence: 90%
“…ANIBES [14,31,32] and enKID [13,30] found a negative association, EsNuPi [13] found different associations according to age, and SI! [15] found a positive association, as did we. Indeed, we found that the HC cluster included a higher proportion of children with obesity (51.1% vs. 46.1%) and overweight (29.0% vs. 19.7%), and a lower proportion with normal weight (19.9% vs. 36.2%) than the SP cluster.…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, in Spain, there have been four previous studies including large samples of children or adolescents, which also found healthy dietary patterns in their study populations by using different approaches, labeling them as "healthy" (enKID [13,30] and SI! [16]), or "Mediterranean-like" (ANIBES [14,31,32] and EsNuPi [15]), including a high intake of vegetables, fruits and fish, similar to our HC.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations